INFLUENCE OF INTELLECTUAL CAPITAL AND CSR DISCLOSURE ON COMPANY VALUE WITH FOREIGN OWNERSHIP STRUCTURE AS MODERATING VARIABLES - Agus Ismaya Hasanudin; Morlia Hindriani; Iis Ismawati (International Journal Labs, 2022)
This study aims to determine the effect of intellectual capital and corporate social responsibility disclosure on firm value with foreign ownership structure as a moderating variable. The object of research used is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This research is a type of quantitative research with secondary data based on the company's annual report obtained from the official website of the Indonesia Stock Exchange. Data processing uses the SPSS 25 application program with multiple linear regression research models and moderated regression analysis (MRA). The results showed that intellectual capital had a negative effect on firm value and CSR disclosure had a significant positive effect on firm value, while foreign ownership structures were unable to moderate the influence of intellectual capital and CSR disclosure on firm value.